C-to-G Base Editing Enhances Oleic Acid Production by Generating Novel Alleles of FATTY ACID DESATURASE 2 in Plants - Park, Mid-Eum; Yun, Jae-Young; Kim, Hyun Uk (Frontiers in Plant Science, 2021)
The demand for vegetable oil, which is mainly used for dietary purposes and cooking, is steadily increasing worldwide. It is often desirable to reduce unsaturation levels of fatty acids in order to increase storage stability and prevent vegetable oils turning rancid and to reduce the amount of trans-fat generation during cooking. Functional disruption of FATTY ACID DESATURASE 2 (FAD2) prevents the conversion of monounsaturated oleic acid to polyunsaturated linoleic acid, thereby enhancing the production of the desirable oleic acid. However, FAD2 null alleles are impractical for agronomical purposes due to their growth defects under stress conditions. Here, we aimed to attenuate FAD2 activity in planta while avoiding adverse growth effects by introducing amino-acid substitutions using CRISPR base editors. In Arabidopsis we applied the adenine base editor (ABE) and cytosine base editor (CBE) to induce semi-random base substitutions within several selected FAD2 coding regions. Isolation of base-edited fad2 alleles with higher oleic acid revealed that the CBE application induced C-to-T and/or C-to-G base substitutions within the targeted sequences, resulting in an alteration of the FAD2 enzyme activities. For example, fad2-144 with multiple C-to-G base substitutions showed less growth defects but with significant increase in oleic acids by 3-fold higher than wild type. Our “proof-of-concept” approach suggests that the equivalent alleles may be recapitulated in vegetable oil crop via precision genome editing for practical cultivation. Our targeted semi-random strategy may serve as a new complementary platform for in planta engineering of useful agronomic traits.